The effect of bagasse pith xylose on yeast growth kinetic in bio-products manufacture - Seyyedeh Sheyda Shafiei Amrehei; esmaeil Rasooly Garmaroody; seyedrahman Djafari Petroudy; omid ramezani (Iranian Journal of Wood and Paper Industries, 2018)
In order to Xylan extraction, bagasse pith, after alkaline pre-treatment and sodium chlorite bleaching, treated with different dosage of soda and then calculated extraction percentage and characterized with FT-IR. Produced xylan changed to xylose with diluted acid hydrolysis and after treatment with active carbon and ultrasonic, reduced sugar measured by HPLC. Then, obtained xylose was added to yeasts media of kluyveromyces marxianus and pichia stipites to evaluate its effects on their growth kinetic. Results showed that by increasing in soda dosage, xylan extraction percentage increased. Also, hydrolysis process alone can produced much sugar without active carbon and ultrasonic. Evaluation of yeasts growth kinetic showed that the speed of yeast growth in media including xylose was more than glucose one and so efficiency of these yeasts is much for C5 sugar as it can be used them for bio-products manufacture.